2018
DOI: 10.1080/19393210.2017.1419509
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate residues in Swiss market foods: monitoring and risk evaluation

Abstract: A total of 243 samples of diverse foodstuffs were analysed for glyphosate and aminomethylphosphonic acid (AMPA) using a liquid chromatography triple quadrupole mass spectrometry (LC/MS/MS) method with a relatively low limit of quantification in the range of 0.0005-0.0025 mg kg. Main contributors for dietary glyphosate and AMPA intake were cereals and pulses. The results suggest that pasta is a very important foodstuff for dietary glyphosate residue intake in Switzerland. Interestingly all samples of wine, frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 12 publications
3
77
1
2
Order By: Relevance
“…Glyphosate is administered only a few days before harvest, which may result in higher glyphosate and AMPA residues. Studies that measured glyphosate residues in diverse food items show that pulses and their products are always in the group with the highest glyphosate load (BVL 2013(BVL , 2014(BVL , 2015(BVL , 2016(BVL , 2017(BVL , 2018(BVL , 2019Stephenson et al 2018;Zoller et al 2018). However, in almost all cases, the measured residues were below the legally tolerated maximum residue levels (MRLs), which in the case of lentils (dry) was raised from 0.1 mg/kg to 10 mg/kg in 2012 in the EU (EFSA 2012; European Union (EU) 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glyphosate is administered only a few days before harvest, which may result in higher glyphosate and AMPA residues. Studies that measured glyphosate residues in diverse food items show that pulses and their products are always in the group with the highest glyphosate load (BVL 2013(BVL , 2014(BVL , 2015(BVL , 2016(BVL , 2017(BVL , 2018(BVL , 2019Stephenson et al 2018;Zoller et al 2018). However, in almost all cases, the measured residues were below the legally tolerated maximum residue levels (MRLs), which in the case of lentils (dry) was raised from 0.1 mg/kg to 10 mg/kg in 2012 in the EU (EFSA 2012; European Union (EU) 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Organic foods have lower levels of pesticide residues. For example, in a Swiss study, 86% of the organic food samples showed no detectable glyphosate residues (Zoller et al 2018). In consequence, exposure to pesticides including glyphosate can be anticipated to be considerably lower when mainly organic foods are consumed (Hyland et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The use of glyphosate causes a global contamination not only in the soil, the surface and underground waters, and the atmosphere, but also in human and animal foods and objects of common use, such as diapers, medical gauze, and feminine hygiene products (Torretta et al 2018;Zhao et al 2018). In food and beverage contamination, glyphosate residues was found in cereals-based products (Liao et al 2018), both conventional and organic honeys (Rubio et al 2013), in legumes (Çetin et al 2017), in beer (Jansons et al 2018) and wine and fruit juice (Zoller et al 2018). Glyphosate was then detectable in human milk (Torretta et al 2018) and urine (Conrad et al 2017;Connolly et al 2018).…”
Section: Glyphosate and Public Healthmentioning
confidence: 99%
“…In 2018, Zoller et al found GLYP at very low levels in 15 of 16 honey samples analyzed; in addition, they also analyzed pulses (tofu and soy sauce), breakfast cereals (corn flakes and pops), durum wheat, pastry and snacks (crisps, etc. ), bread, flour and baking mixtures, and beverages (beer, wine, milk, fruit juices, and mineral water) for a total of 243 samples [86]. The authors applied a well-tested analytical method based on solvent extraction with methanol and LC-MS/MS analysis for determining GLYP and AMPA (LODs 0.2-0.4 and 0.5-1 μg kg −1 , respectively; LOQs 0.5-1 and 1-2.5 μg kg −1 ; recoveries 92-103 and 92-115%; RSDs <9.5 and <13.9%).…”
Section: Honeymentioning
confidence: 99%